2021
DOI: 10.1186/s13063-020-04976-x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human C1 esterase inhibitor (conestat alfa) in the prevention of severe SARS-CoV-2 infection in hospitalized patients with COVID-19: A structured summary of a study protocol for a randomized, parallel-group, open-label, multi-center pilot trial (PROTECT-COVID-19)

Abstract: Objectives Conestat alfa, a recombinant human C1 esterase inhibitor, is a multi-target inhibitor of inflammatory cascades including the complement, the kinin-kallikrein and the contact activation system. The study objective is to investigate the efficacy and safety of conestat alfa in improving disease severity and short-term outcome in COVID-19 patients with pulmonary disease. Trial design This study is an investigator-initiated, randomized (2:1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Open queries such as biomarkers of response and long-term benefit are still pending. Real-world studies, such as OPTIMISE-C19, will be critical in providing information on the long-term efficacy to prevent hospitalizations and mortality within the subgroups of high-risk patients as well as sustained symptomology resolution of monoclonal antibodies [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open queries such as biomarkers of response and long-term benefit are still pending. Real-world studies, such as OPTIMISE-C19, will be critical in providing information on the long-term efficacy to prevent hospitalizations and mortality within the subgroups of high-risk patients as well as sustained symptomology resolution of monoclonal antibodies [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones are increasingly integrated in scientific research and have been used in the past to measure PA [ 51 ]. Furthermore, a recent study demonstrated the use and value of smartphones in facilitating behavioral interventions (including PA) in pregnant women [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial has investigated the effect of melatonin consumption on controlling arterial pressure and anthropometric indices in type 2 diabetes mellitus patients. It reduced significantly the mean level of systolic pressure, mean arterial pressure, pulse pressure, and conicity index in the intervention group [ 44 ]. In addition, the chronobiotic properties of melatonin have been evaluated.…”
Section: Biological Activities Of Melatoninmentioning
confidence: 99%